الكفايات اللازمة لاختيار القيادات الأكاديمية بسلطنة عمان في ضوء رؤية استراتيجية التعليم 2040 - العاني، وجيهة ثابت; الشيدية، فائزة بنت أحمد بن محمد; الكيومية، أمل راشد عبدالله (جامعة الزرقاء - عمادة البحث العلمي, 2021)
This study aims to search for the necessary competencies to choose academic leaders in the Sultanate of Oman in light of the vision of the 2040 education strategy. To achieve this aim, a qualitative approach is used, by preparing an interview card that includes five main questions. The sample of the interview consists of nine individuals who occupy leadership positions at the university and whose work is related to the educational field. The sample consists of (the dean of the faculty and his assistants, a sample of department heads, the dean of admission and registration, directors of centres, and the head of the Quality and Accreditation Unit). The data collection period took about one month. The qualitative method is used to analyse the responses of the corresponding sample using the coding system NVivo according to the study fields. \nThe results of the study show that one of the most important competencies mentioned in the responses is the following competencies: personal competencies, professional competencies, communicational competencies, planning competencies, adequacy of practices, and technological competencies, in addition to the importance of academic leaders possessing the cognitive ability in two main dimensions (academic specialization and professional specialization). Furthermore, there is the importance of having a cultural horizon that helps them deal with various groups of society. As for the factors that influence the academic leader's success and make him distinguished, these are his ability to work with others, to take responsibility, to have the drive for accomplishments, to have the ability to negotiate and conclude deals, and to have the ability to deal with crises or risks. Based on the results of the study, several recommendations and proposals are developed.
تهدف هذه الدراسة إلى البحث عن الكفايات اللازمة لاختيار القيادات الأكاديمية بسلطنة عمان في ضوء رؤية استراتيجية التعليم 2040. وقد تم استخدام المنهج النوعي من خلال إعداد بطاقة مقابلة تضمنت خمسة أسئلة رئيسة. وتكونت عينة المقابلة من تسعة أفراد ممن يشغلون مناصب قيادية في الجامعة ويرتبط عملهم بالمجال الأكاديمي، وتمثلت عينة الدراسة في: (عميد الكلية ومساعدوه، وعينة من رؤساء الأقسام، وعميد القبول والتسجيل، ومديرو المراكز ورئيس وحدة الجودة والاعتماد). واستغرقت مدة جمع البيانات حوالي شهر، كما تم استخدام المنهج النوعي في تحليل استجابات عينة المقابلة باستخدام نظام الترميز باستخدام برنامج (NVivo) وفقا لمحاور الدراسة. \nومن أهم النتائج التي أظهرتها الدراسة، أن هناك العديد من الكفايات التي يجب أن يمتلكها القياديون: كفايات شخصية، وكفايات مهنية، وكفايات التواصل، وكفايات التخطيط، وكفاية التأمل في الممارسات، وكفايات تكنولوجية، إضافة إلى أهمية امتلاك القادة الأكاديميين القدرة المعرفية في بعدين رئيسيين (التخصص الأكاديمي، والتخصص المهني)، إضافة إلى امتلاكهم آفاقا ثقافية تساعدهم في التعامل مع مختلف فئات المجتمع. أما بالنسبة إلى العوامل التي تؤثر في نجاح القائد الأكاديمي وتجعله متميزا فقد تتمثل بقدرته في العمل مع الآخرين، وتحمل المسؤولية، والدافع للإنجاز، وامتلاك القدرة على التفاوض، وعقد الصفقات، والقدرة في التعامل مع الأزمات أو المخاطر. وبناء على نتائج الدراسة تم وضع العديد من التوصيات والمقترحات.
Keywords: الكفايات التعليمية -- القيادات الأكاديمية -- المؤسسات التعليمية -- سلطنة عمان